The early changes of seminiferous tubular boundary zone and elastic fibers in vasectomized young rats: Light and electron microscopic study - (:unkn) unknown (MEDIMOND PUBLISHING CO, 2001)
Vasectomy is a contraceptive method widely used in the world, after which seminiferous tubules degeneration and interruption of spermatogenesis take place. The boundary zone and elastic fibers play an important role in the function of the seminiferous tubules. We investigated these structures in young Wistar-Albino rats after bilateral vasectomy. The animals were set in 4 experimental groups: Sham group (only abdominal incision), 2 weeks, 6 weeks and 12 weeks groups following vasectomy. Significant increase in seminiferous tubules degeneration and a decrease, sometimes loss in elastic fibers was observed in concordance with the changes of the boundary zone: thickening of basement membrane, myoid cell granulation etc. The loss or absence of the elastic fibers in our study is based on the diminished spermatogenesis, which may lead to a generalized atrophy of the testes in vasectomized rats.
Keywords: LAMINA PROPRIA